Antiviral and Virucidal Activities of Camptothecin on Fowl Adenovirus Serotype 4 by Blocking Virus Replication - Yin, Dongdong; Yin, Lei; Wang, Jieru; Shen, Xuehuai; Dai, Yin; Zhao, Ruihong; Hu, Xiaomiao; Hou, Hongyan; Zhang, Danjun; Wang, Guijun; Qi, Kezong; Pan, Xiaocheng (Frontiers in Cellular and Infection Microbiology, 2022)
Fowl adenovirus serotype 4 (FAdV-4) caused hepatitis–hydropericardium syndrome in poultry and caused huge economic losses to the poultry industry. At present, antiviral drugs effective against this virus have not been reported yet, and new treatment methods are urgently needed to prevent and control FAdV-4. Camptothecin has been shown to have antiviral activity against various viruses; however, whether it can inhibit FAdV-4 infection remains unclear. This study aimed to explore the anti-FAdV-4 effects and mechanisms of camptothecin in vitro and in vivo. Several camptothecin treatments were used to study the antiviral activity of camptothecin on FAdV-4-infected Leghorn male hepatocellular (LMH) cells. The FAdV-4 titers of mock and camptothecin-treated infected cell cultures were determined using tissue culture infective dose assay, and the FAdV-4 copy number was determined using quantitative real-time polymerase chain reaction. In addition, the therapeutic effect of camptothecin on FAdV-4-infected chickens was also evaluated. The results showed that camptothecin significantly reduced the viral infection in LMH cells in a dose-dependent manner, resulting in a reduction in viral titer, viral copy number, and viral Hexon protein expression. Camptothecin was also found to have a significant inhibitory effect on the virus replication step. Finally, camptothecin showed anti-FAdV-4 efficacy in the chicken infection model, and the survival rate significantly improved. This study was novel in proving that camptothecin had a protective effect on FAdV-4, indicating its potential as an antiviral drug against FAdV-4 infection.